2022
DOI: 10.3390/agronomy12061395
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting Fluorescent Pseudomonas from the Brazilian Amazon for the Biocontrol of Signal Grass Foliar Blight

Abstract: Biological control is considered the only viable integrated disease management practice for controlling the widely distributed and destructive foliar blight and sudden death disease caused by the fungus Rhizoctonia solani AG-1 IA on signal grass (Urochloa brizantha) pastures. Since major signal grass varieties are highly susceptible and fungicide sprays are not labeled for grass pasture cropping systems, biological control is sought as an alternative for managing this fungal disease. In this study, 24 fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The control of phytopathogenic fungi using bacteria of the genus Pseudomonas (Rodriguez and Pfender, 1997, Yang et al, 2014, Vicentini et al, 2022, Pantoea (Dutkiewicz et al, 2016), and Bacillus (Ferraz et al, 2008, Bach et al, 2016 has been reported in the scientific literature. According to Asaturova et al (2022), when using B. velezensis against D. tritici-repentis, a reduction in the mycelial growth of pathogens of up to 94.3% was observed at 15 days in in vitro tests.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The control of phytopathogenic fungi using bacteria of the genus Pseudomonas (Rodriguez and Pfender, 1997, Yang et al, 2014, Vicentini et al, 2022, Pantoea (Dutkiewicz et al, 2016), and Bacillus (Ferraz et al, 2008, Bach et al, 2016 has been reported in the scientific literature. According to Asaturova et al (2022), when using B. velezensis against D. tritici-repentis, a reduction in the mycelial growth of pathogens of up to 94.3% was observed at 15 days in in vitro tests.…”
Section: Resultsmentioning
confidence: 99%
“…promoting growth, assisting in obtaining nutrients, and promoting the induction of resistance to diseases and pests by activating metabolic pathways of plant physiology (Dutkiewicz et al, 2016). These characteristics are also present by some species of the genus Bacillus (Bach et al, 2016) and Pseudomonas (Vicentini et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations